The Influence of the Non-Physical Work Environment and Work Satisfaction on the Work Enthusiasm of Civil Servants of the Population and Civil Registration Office of Pontianak - Awan Kusuma; Eru Ahmadia (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2025)
The effectiveness of civil servants in achieving organizational goals is greatly influenced by various factors, including work environment and job satisfaction. This study aims to determine the effect of non-physical work environment and job satisfaction on the work spirit of civil servants at the Pontianak City Population and Civil Registration Office. This study uses a quantitative approach with an associative method, using primary data collected through questionnaires and interviews. Secondary data were employee performance appraisals and records of violations. The sample consisted of 49 respondents selected using the saturated sampling technique. Data analysis was performed using IBM SPSS 26, which included validity and reliability tests, classical assumption tests, and hypothesis tests through multiple linear regression analysis. The results showed that the non-physical work environment had a significant positive effect on work enthusiasm, while job satisfaction did not show a significant effect. The coefficient of determination (R²) is 0.239, which indicates that 23.9% of the variation in work enthusiasm is explained by the non-physical work environment and job satisfaction, while the remaining 76.1% is caused by other variables. This study concludes that improving the non-physical work environment can positively influence work enthusiasm, which in turn can improve employee performance.